Dynamics of Deviant Behavior of Adolescents in the Digital Era: A Qualitative Study in Tangga Village, Monta District, Bima Regency - Irman Susanto (JUPE : Jurnal Pendidikan Mandala, 2026)
The development of digital technology has brought significant changes to adolescents' lifestyles, particularly in terms of social interaction and daily behavior. Easy access to the internet and social media provides various benefits; however, it also has the potential to encourage behaviors that deviate from the values and norms prevailing in society. This study aims to describe the forms of juvenile deviant behavior in the digital era, identify the factors contributing to such behavior, and analyze the efforts undertaken to address it in Tangga Village, Monta District, Bima Regency. This research employed a qualitative approach with a descriptive research design. Informants were selected purposively and consisted of adolescents, parents, community leaders, religious leaders, youth leaders, and village officials. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through source and method triangulation.The findings reveal that the forms of deviant behavior among adolescents in the digital era include excessive use of social media, promiscuity, declining obedience to parents, and reduced participation in social and religious activities. The factors influencing these behaviors include a lack of parental supervision, peer influence, easy access to digital technology, and weakened social control within the community. Efforts to address these issues include strengthening parental supervision, enhancing religious and character education, revitalizing youth activities, and fostering collaboration among families, schools, communities, and village governments. This study highlights the importance of digital literacy and the reinforcement of social values in shaping positive adolescent behavior in the digital era.